1982
DOI: 10.1139/z82-203
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of the larval antenna of Tenebrio molitor L. (Coleoptera: Tenebrionidae): structure of the blunt-tipped peg and papillate sensilla

Abstract: Each antenna of a final instar Tenebrio molitor larva has two blunt-tipped pegs and two papillate sensilla. The former are short pegs with fluted cuticle and a terminal moulting pore and are set in deep sockets. Two large microtubule-filled dendrites fill a dense dendritic sheath within the peg; below the base of the peg they are joined by a lamellate dendrite and a dendrite resembling a scolopidial cilium. There are four accessory cells, the innermost resembling a scolopale cell. This sensillum may be thermo-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1984
1984
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Sensilla basiconica have the role of contact chemoreceptors [26]. Trichoid sensilla present on galea and maxillary palps have an olfactory role [51]. Bland et al [52] suggested that these sensilla are involved in the chemoreception of pheromones.…”
Section: Discussionmentioning
confidence: 99%
“…Sensilla basiconica have the role of contact chemoreceptors [26]. Trichoid sensilla present on galea and maxillary palps have an olfactory role [51]. Bland et al [52] suggested that these sensilla are involved in the chemoreception of pheromones.…”
Section: Discussionmentioning
confidence: 99%
“…Ch-like features include the presence of the well-developed ciliary rootlet and welldeveloped zonula adherens junctions with the scolopale cell. Although this particular type was not recorded in the only ultrastructural investigation of this organ in (Bloom et al, 1982). C: A range of crustacean mechanoreceptive sense organs.…”
Section: Intermediate Forms Of Sense Organs In Insectsmentioning
confidence: 97%
“…A further form of sense organ with mixed neuronal types is the es organ with a single ch-like neuron (Altner and Thies, 1984;Altner et al, 1978;Bloom et al, 1982;Crouau et al, 1987). These multiinnervated sensilla are es-like in most ways except that one ch-like neuron terminates beneath the cuticular peg of a thermo-hygroreceptive sense organ or a chemoreceptive hair (Fig.…”
Section: Intermediate Forms Of Sense Organs In Insectsmentioning
confidence: 99%
“…With this technique, we have identified probable gustatory sensilla on the antennae and the maxillary and labial palps of Tenebrio molitor larvae. Bloom et al (1982a) suggested that the aporous long trichoid and the multiporous U-shaped placoid sensilla on the antennae of T.molitor larvae were chemosensilla based on the morphology of their sensory cuticles and their innervation. Neither type is permeable to aqueous CO++, and therefore both probably respond to lipophilic rather than hydrophilic compounds.…”
Section: Permeability Of Sensillamentioning
confidence: 99%
“…They described the fine structure of four types of the antennal exterosensilla and, based on this morphology, proposed the following functions. The long aporous hairs on the flagellar tip were presumed to be chemosensory with perhaps some degree of chemospecificity, and the long uniporous pointed pegs on the flagellum and pedicel which are structurally similar to gustatory pegs wcrc considered to have chemosensory and mechanosensory neurones (Bloom et al, 1982a). The unique papillate plates with a central pore were presumed to be gustatory sensilla also, and the aporous short blunt-tipped pegs were assigned a putative thermo-hygrosensing func-tion (Bloom et al, 1982b).…”
Section: Introductionmentioning
confidence: 99%